Unnecessary orchiectomy due to atypical sarcoidosis manifesting as a unilateral scrotal mass: a case report and literature review - Skopelidou, Valeria; Hurník, Pavel; Židlík, Vladimir; Tulinský, Lubomír; Lenz, Jiří; Balner, Tomáš; Žiak, Dušan; Delongová, Patricie; Karas, Rudolf; Škripková, Miroslava; Jendřejek, Matěj (Frontiers in Immunology, 2023)
Sarcoidosis is a disease characterised primarily by lung tissue involvement. Extrapulmonary involvement, particularly in the genitourinary tract, is extremely rare, particularly when it comes to primary disease detection in this location. The gold standard in establishing a definitive diagnosis of sarcoidosis is a combination of the clinical picture, the results of imaging methods, and histopathological examination from the biopsy taken (thus ruling out other causes of granulomatous inflammation). However, it is common for the biopsy to be infeasible or for the patient to refuse such an examination, resulting in the neglect of this critical verification. We introduce the case of a young 29-year-old man of Czech nationality who had been complaining for some time about non-specific pain above the pubic bone and in the lower abdomen, which was combined with a painless enlargement of the right half of the scrotum. Due to suspected malignancy, it was, after considering clinical, imaging, and laboratory findings, decided to perform a radical orchiectomy as a treatment option. The histological examination revealed that it was not cancer, but rather a rare genitourinary form of extrapulmonary sarcoidosis. In this case, radical resection had been, therefore, unnecessary. We also present a review of the literature on published extrapulmonary, genitourinary, and testicular sarcoidosis cases. All the above demonstrates the importance of considering a possible atypical sarcoidosis manifestation and histological confirmation before pursuing radical solutions.